Faktor-Faktor yang Berhubungan dengan Penerapan Keselamatan Pasien oleh Perawat Pelaksana dalam Implementasi Program Berani Sehat - Arniawan Arniawan; I Made Rio Dwijayanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to analyze the factors associated with the implementation of patient safety by staff nurses in the implementation of the Berani Sehat program. The study employed a quantitative method with a cross-sectional approach. Data were analyzed using univariate and bivariate analyses with the Gamma test. The results showed that there were significant relationships between knowledge (γ = 0.897; p = 0.000), length of service (γ = 0.898; p = 0.000), and nurses’ age (γ = 0.843; p = 0.000) with the implementation of patient safety. Meanwhile, educational level was not significantly associated with the implementation of patient safety (γ = 0.417; p = 0.324). In conclusion, individual factors such as knowledge, length of service, and age play an important role in the implementation of patient safety by staff nurses. Keywords: Patient Safety, Staff Nurses, Berani Sehat Program